Implementation of the Prophet's Preaching Method by Preachers in the Digital Era - Ulpa Apipah, Neng (Islamic Journal of Communication and Public Discourse, 2025)
Background: The rapid development of digital technology has significantly transformed Islamic preaching (da’wah), requiring contemporary preachers (da’i) to reinterpret prophetic methodologies within algorithm-driven social media environments. Although prophetic principles wisdom (hikmah), beautiful preaching (mau’izhah hasanah), reasoned argumentation (mujadalah bi-llati hiya ahsan), and gradual progression (tadrij) remain timeless, their implementation in digital contexts demands contextual adaptation without compromising theological authenticity.Objective: This study aims to examine how digital da’i understand, interpret, and implement prophetic preaching methods across various social media platforms while navigating technological and algorithmic pressures.Method: This research employs a qualitative phenomenological approach involving 23 digital da’i selected through purposive sampling. Data were collected through in-depth interviews, analysis of 287 digital artifacts across YouTube, Instagram, TikTok, Facebook, and WhatsApp, non-participatory observation, and document analysis. Data were analyzed using a six-phase thematic analysis framework.Findings and Implications: The findings reveal three interpretive frameworks: classical adaptation (35%), contextualized translation (48%), and innovative integration (17%). Implementation strategies operate across five domains: content conceptualization, communication style, visual design, structural organization, and audience engagement. The study also identifies tensions between algorithmic demands for engagement and prophetic commitments to spiritual depth and ethical communication.Conclusion: The study highlights the need to integrate digital communication competencies into Islamic da’wah education while preserving prophetic foundations. Prophetic da’wah remains relevant in the digital era when applied with contextual wisdom, ethical integrity, and strategic adaptation.